Professionalization, Insertion, Mobility and Professional Status. A Comparative Analysis in Populations of Doctors - Aparicio, Miriam Teresita (2016)
This study is in line with the analyses of university and working career in their interaction in relation with conditioning factors, carried out by Dr. Aparicio for the past two decades with a variety of populations.t. The aim was to analyze the relation between working conditions and future working perspectives through social representations. There are three core variables: Professional Mobility, Professional Status and perspectives regarding the future of their careers at the personal development level and within the organizations, considering, on the one hand, insufficient Professionalization and the increasing market demands; and on the other the impact structural limits have on the identity level. The methodology used was quanti-qualitative (semi-structured questionnaires, interviews, and hierarchical evocations, out of which we will analyze one node: Labor Market). The population consisted of doctors (2005-2012) from the National University of Cuyo, in Argentina and the CNAM (France) of different courses of study. The analysis is done from a systemic sui generis perspective involving three interwoven levels (macro-meso-micro-macro), called The Theory of the Three-Dimensional Spiral of Sense (See Aparicio, 2015 c and d; also, 2005 2007a; 2007b, 2013a, 2014 b; 2015 c, 2015 d). The results show that it enters in the nucleus of such representations, which relates to the current issue of professional mobility, as regards different study courses and contexts; we can also observe the effect of professionalization on the insertion environment, and on the personal and organizational identity.